Children's Guide to Insects and Spider - Johnson, Jinny; Nang ChanYeema (New York, USA Simon and Schuster, 1996)
Provides an introduction to more than 100 insects and arachnids, giving general information about family characteristics and habits, and more specific facts about some species.
Keywords: Juvenile Nonfiction